BIG DATA TO FIND OUT THE RELATIONSHIP BETWEEN LABORS DEMAND AND SUPPLY WITH SEARCH INDEXES GOOGLE TRENDS - Roosganda Elizabeth; Geraldy Samuel Ivan; Giovanni Inez Erika Margaretha; Didik Notosudjono; Martinus Tukiran; Widodo Sunaryo; Didit Ardianto; Nancy Yusnita; Yayan Hadiyat (Laboratorium Riset Ekonomi, 2023)
The study aims to observe the dynamics of unemployment rate and the number of job openings in Java as the region that becomes the main crutch of the Indonesian economy and analyze the relationship between supply and demand of labor in during the pandemic using Web Scraping and Pearson correlation analysis. Web scraping results show that the largest number of job openings in Java Island early 2021 are in West Java and DKI Jakarta and the most demanded jobs are sales, marketing, followed by administration staff, low-level accounting, and finance. The correlation analysis shows a weak positive relationship of 0.45 between labor market supply and demand using the keyword” Lowongan Kerja” based on the google trends search index and a moderate positive of 0.54 using the keyword ”Loker” on the google trends search index.